Functional problems after surgical treatment of spine fractures - Agnieszka Nowacka; Kamila Woźniak-Dąbrowska; Wojciech Smuczyński (Kazimierz Wielki University, 2021)
Introduction: Despite the large amount of research on the spine injuries themselves and on methods of their treatment, there are only a few reports of functional problems faced by patients after surgical treatment of these injuries. Aim: The aim of the study was to demonstrate the occurrence of functional problems and determine their type in patients after surgical treatment of spinal injuries, to determine the impact of the severity of the injury on the occurrence of dysfunctions, to determine the impact of patients' health and fitness on the occurrence of functional problems and coping with them, to demonstrate the relationship between the mental state and the occurrence of dysfunction, determination of the impact of pain on the occurrence of functional problems, assessment of the degree of coping with dysfunctions. Materials and methods: The study included a group of 20 people (13 men and 7 women) treated surgically at the Department of Neurosurgery, Nicolas Copernicus University Collegium Medicum in Bydgoszcz, due to a spine injury. The average age of the respondents was 44.6 years. The research consisted of patient answering the questions included in the patient's questionnaire, subjective descriptive test of pain intensity, modified Barthel scale and determination of pain intensity on the VAS scale. The investigator also completed an additional questionnaire in order to obtain additional information about the patient's health. Results: Research results indicate pain as the main cause of postoperative dysfunction. They concern self-service activities, travel, sleep and social life. As it has been shown on the basis of research, the quality of coping with functional problems depends on factors such as physical fitness, the activity of daily life before the injury, the presence of comorbidities, mental attitude and the severity of the injury.